Dorsiflexion shoes affect joint-level landing mechanics related to lower extremity injury risk in females - Garcia, G. L.; Caminita, M.; Hunter, J. G.; Miller, R. H.; Shim, J. K. (Sports Biomechanics, 2025)
Athletic shoes that induce dorsiflexion in standing can improve jump height compared to traditional athletic shoes that induce plantarflexion, but it is unknown if dorsiflexion shoes (DF) also affect landing biomechanics associated with lower extremity injury risk. Thus, the purpose of this study was to investigate if DF adversely affect landing mechanics related to patellofemoral pain and anterior cruciate ligament injury risk compared to neutral (NT) and plantarflexion (PF) shoes. Sixteen females (21.65 ± 4.7 years, 63.69 ± 14.3 kg, 1.60 ± 0.05 m) performed three maximum vertical countermovement jumps in DF (-1.5°), NT (0°) and PF (8°) shoes as 3D kinetics and kinematics were recorded. One-way repeated-measures ANOVAs revealed peak vertical ground reaction force, knee abduction moment and total energy absorption were similar between conditions. At the knee, peak flexion and joint displacement were lower in DF and NT, while relative energy absorption was greater in PF (all p < .01). Conversely, relative ankle energy absorption was greater in DF and NT compared to PF (p < .01). Both DF and NT induce landing patterns that may increase strain on passive structures in the knee, emphasising the need for landing mechanics to be considered when testing footwear as gains in performance could come at the cost of injury risk.